Cytosine nucleoside inhibition of the ATPase of Escherichia coli termination factor rho: evidence for a base specific interaction between rho and RNA. - Richardson, L V (1992)
The function of rho factor in transcription termination depends on interactions with nascent RNA molecules that contain unpaired cytidylate residues. We show that cytidine, as a free nucleoside, inhibits the binding of rho to lambda cro mRNA and is a competitive inhibitor of rho-ATPase activity with lambda cro mRNA as cofactor. The relative ability of various cytidine analogs and other nucleosides to inhibit the rho-RNA interaction was used to probe features responsible for the base specificity of rho action. The results suggest that rho has a specificity pocket in its polynucleotide-binding site that apparently can make H-bond interactions with the side of the cytosine ring that normally faces away from the sugar ring and that may involve a relatively close fit along the edge of the ribose ring at the C2' carbon. The nature of the complex of rho with cytidine nucleotides was analyzed further by determining whether incubation with BrCMP caused inactivation of rho ATPase. Although BrCMP could form Michaelis inhibition complexes, it did not activate rho. Rho thus lacks a diagnostic property of enzymes that make specific covalent addition complexes with pyrimidines.